Getting Shut Out of the International Capital Markets : It Doesn't Take Much - Marion, Nancy; Flood, Robert (Washington, D.C. : International Monetary Fund, 2006)
We use a simple model of international lending to show that an emerging market borrower who might default can be shut out of international capital markets without warning. A modest haircut on obligations, for example, can shut down lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet